Comparison of kinematics characteristics of different techniques in volleyball spike - Bu, Y.; Li, S.; Wang, L.; Wang, A.; Zhang, X.; Liu, X. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume II: Bio-Mechanics and Sports Engineering., 2008)
Spike techniques in volleyball included bended-arm technique, swing-arm technique and straight-arm technique. The comparison of kinematics characteristics of three spike techniques were investigated with the methods of sports biomechanics to get the kinematics characteristics of the three different spike techniques and differences among them. The research showed that the three techniques exerted different efforts under different condition.